Evaluation of occupational tuberculosis prevention in a brazilian hospital - Eni Hilario Silva; Maria Clara Padoveze; Arnaldo Toyokazu Tanaka; Raquel Carneiro Machado Higa; Lubiana Guilherme Americo Cavalcante (Universidade Federal do Ceará, 2015)
Objective: to assess the institutional processes for preventing occupational tuberculosis. Methods: this is a quasi-experimental research in a pre and post-intervention model (3 phases), conducted in a Brazilian hospital. They used specific quality indicators for assessment structure (physical and educational resources) and process (52 direct observations of compliance to the use of N95 mask at each stage). Results: the compliance rates were 33.0% and 94.2% in the pre-intervention phase; and 44% and 100% in the post-intervention phase, respectively, for structure and process. The interventions designed from the initial results of indicators (pre-intervention phase) were structural and educational. Conclusion: there was an improvement of the indicators in the post-intervention phase from the interventions performed, which contributed to improved quality of service.